2021
DOI: 10.20950/1678-2305.2020.46.4.554
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Ornamental Fish Exports From the Amazon State, Brazil

Abstract: The updated status of the ornamental fish trade from the Amazonas state was analyzed between the years of 2006-2015 (IBAMA database). The trade of ornamental fish from Amazonas state mainly consists of species extracted from nature. A total of 142,552,253 specimens were exported during the studied period. Sales plummeted since 2006, from 26,075,241 specimens exported then to 2,729,846 specimens in 2015 (Jan-Jul). Between 2006 and 2015, a total of US$ 23.0 million in revenue was generated from fish exports dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Prior to the present study, three Leporinus species were considered to be present in the hydrographic basins of the Brazilian state of Maranhão— L. affinis , in the Itapecuru basin( Abreu et al, 2019 ), L. friderici in the Itapecuru, Mearim, Maracaçumé, Munim, Periá, and Parnaíba basins ( Piorski et al, 1998 ; Soares, 2005 ; Ramos, Ramos & Ramos, 2014 ; Melo et al, 2016 ; Abreu et al, 2019 ; Brito et al, 2019 ; Brito et al, 2020 ; Guimarães et al, 2021a ; Guimarães et al, 2021b ; Guimarães et al, 2021c ), and L. piau in the basins of the Itapecuru, Mearim, Turiaçu, and Parnaíba rivers ( Barros, Fraga & Birindelli, 2011 ; Ramos, Ramos & Ramos, 2014 ; Ribeiro et al, 2014 ; Assega & Birindelli, 2019 ; Abreu et al, 2019 ). Based on analyses of molecular data, however, Fraga et al (2014) and Nascimento et al (2016) found evidence of two distinct lineages in the L. piau group from the Itapecuru basin, while in the present study, L. piau was assigned to three different clades, being associated strongly with L. cf.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the present study, three Leporinus species were considered to be present in the hydrographic basins of the Brazilian state of Maranhão— L. affinis , in the Itapecuru basin( Abreu et al, 2019 ), L. friderici in the Itapecuru, Mearim, Maracaçumé, Munim, Periá, and Parnaíba basins ( Piorski et al, 1998 ; Soares, 2005 ; Ramos, Ramos & Ramos, 2014 ; Melo et al, 2016 ; Abreu et al, 2019 ; Brito et al, 2019 ; Brito et al, 2020 ; Guimarães et al, 2021a ; Guimarães et al, 2021b ; Guimarães et al, 2021c ), and L. piau in the basins of the Itapecuru, Mearim, Turiaçu, and Parnaíba rivers ( Barros, Fraga & Birindelli, 2011 ; Ramos, Ramos & Ramos, 2014 ; Ribeiro et al, 2014 ; Assega & Birindelli, 2019 ; Abreu et al, 2019 ). Based on analyses of molecular data, however, Fraga et al (2014) and Nascimento et al (2016) found evidence of two distinct lineages in the L. piau group from the Itapecuru basin, while in the present study, L. piau was assigned to three different clades, being associated strongly with L. cf.…”
Section: Discussionmentioning
confidence: 99%
“…Between 2002 and 2005, approximately 100 million specimens were exported to 35 countries, the year 2005 being the record in sales reaching 36 million specimens representing 169 species and exports generating 2.4 million USD. The Manaus Area housed 16 ornamental fish export companies, but three of them controlled 82 per cent of the market until 2005 [20].…”
Section: Ornamental Fish Tradementioning
confidence: 99%
“…Of the >90 species of dwarf cichlids of the genus Apistogramma , many are harvested from the wild or cultured for the ornamental fish trade in some capacity ( Tribuzy-Neto et al, 2020 ). They are native to South America and are most diverse in the Amazon floodplains, and the diverse array of species with overlapping ranges and habitats can result in the simultaneous capture of multiple species and non-target species of Apistogramma being discarded when not specifically sought by fishers due to market demands and space limitations during capture.…”
Section: Introductionmentioning
confidence: 99%